Theory of chronoamperometry at cylindrical microelectrodes and their arrays - Dickinson, E; Streeter, I; Compton, R (2008)
Potential step chronoamperometry at cylindrical electrodes is modeled using the finite difference method in a two-dimensional (2D) simulation space. Trends are discussed in terms of the cylinder height-to-radius ratio Ze for top-only, side-only, and fully conducting cylinders. The diffusion domain approximation is then used to simulate regular arrays of cylindrical microelectrodes supported on a conducting substrate, comparing the different shapes of chronoamperometric transients for varying Ze, surface coverage Θ, and top/side conductivity. © 2008 American Chemical Society.